Influence of religious values on stakeholder management: The Islamic religious perspective - Benneh, Dennis Diawuo (2021)
A thesis submitted to the Department of Construction Technology and Management, College of Art Built Environment in partial fulfilled of the requirement for the Degree of Master of Science